Penerapan Tsawab dan Iqab dalam Pembelajaran Tahfidz Al-Qur’an di Pondok Pesantren Ihyaus Sunnah Sentong Krejengan Probolinggo - Luluk Masluhah; Mamluatun Ni’mah; Imam Muttaqin (Pendidikan Agama Islam STIT Palapa Nusantara, 2023)
This study aims to determine the form of the application of tsawab and iqab, the supporting and inhibiting factors of tsawab and iqab, and the impact of the application of tsawab and iqab in learning tahfidz Al-Qur'an. This study uses a qualitative method approach with a descriptive approach. This research was conducted at the Islamic boarding school Ihyaus Sunnah Sentong Krejengan Probolinggo class VII Tsanawiyah with a total of 15 students. Data collection techniques are observation and interviews. The findings show that the tsawab given by the teacher to students varies in different ways in the learning process. While iqab is given with a sign, namely: using the eye. Iqab with words that is through words. Iqab by deed, namely by ordering him to stand. Iqab's body is like hitting. Supporting factors, namely internal factors include: the existence of intention, setting a time limit for memorizing according to the target set by the teacher. While external factors include: the existence of motivation from caregivers and teachers, the target in memorizing each week is one surah, while the inhibiting factors are internal factors including: lack of patience in memorizing, lack of intention in memorizing. While external factors include: teachers often come late, guardians of students do not support. As for the positive impact, students become more enthusiastic in memorizing, have a sense of responsibility, and can improve their memorization, students are happy when they get Tsawab and also accept when they get Iqab. While the negative impact is that students feel afraid and ashamed of their friends, but this disappears when students remember events that are in accordance with the theory of punishment, namely as a deterrent.